Pengembangan E-modul Literasi Sains Pada Mata Pelajaran IPA (Fisika) untuk Meningkatkan Keterampilan Proses Sains - Irna Yosa; Muhammad Arsyad; Pariabti Palloan (Postgraduate, University of Mataram, 2025)
This research is a type of Research and Development (R&D) using the Four-D model. The stages are Define, Design, Develop, and Disseminate. The aim is to develop a science literacy e-module for science (physics) subject and to test its validity, practicality, and effectiveness to improve students' science process skills. Three experts checked the content validity of the e-module, teacher questionnaire, and science process skills test. Ten science (physics) teachers tested the practicality, and the effectiveness e-module was tried on 34 students of Grade 8 at SMP Katolik Belibis Makassar. The results show: 1) the e-module is valid and suitable to use, 2) the teachers' response is very practical, and 3) the effectiveness of the e-module is shown by an N-gain score of 63.40%, which means it is effective to improve students' science process skills. Based on these results, the science literacy e-module for science (physics) is valid, very practical, and effective to support the learning process of science process skills.